Isolation Characterization and Purification of Exogenous Protein from Pseudomonas aeruginosa - Viswanathan, K (International Journal of Pharmaceutical & Biological Archive, 2013)
Isolation Characterization and Purification of Exogenous Protein from Pseudomonas aeruginosa